Gambaran Ph Saliva Pada Anak Usia 5-10 Tahun (Kajian Pada Pasien Anak Di Klinik Pedodonsia Fkg Usakti) - Hani Yulia Ningsih; Tri Putriany Agustin (Jurnal Kedokteran Gigi Terpadu, 2019)
Backgrounds: Demineralization of enamel surfaces occurs as a result of a decrease in salivary pH which if occurs without balance together with remineralization can cause caries. According to previous studies about the relationship between pH and caries prevalence, children with a salivary pH <6.6 had a caries risk of 1.36 times higher than with pH> 6.8. Overconsumption levels of food containing a high cariogenic levels cause the pH levels of saliva in children drop below the critical level of 5.5. This study aims to describe distributions of salivary pH in children among 5-10 years old. Materials and Methods: As many as 30 pediatric patients took 10mL of salivary samples and measured using pH meter. Result: A total of 20 children (67%) had pH 6.0-6.6 and no children had a pH of 5.0-5.8 (0%). Conclusion: Salivary pH patients age 5-10 years in the Pediatric Dentistry Clinic FKG Usakti is considered to be acidic, mostly 6.0-6.6. This condition causes children to be at high caries risk.